Histopathological approach to cutaneous lymphoid infiltrate - Uma Nahar Saikia; Manoj Gopal Madakshira (Wolters Kluwer Medknow Publications, 2019)
Cutaneous lymphoid infiltration is common histology seen in the day-to-day practice of dermatopathology. The reasons for this infiltration can range from a spontaneously remitting pseudolymphoma such as Jessner's infiltration to a sinister and aggressive cytotoxic T-cell lymphoma. Before analyzing the slide, the clinical perspective needs to be borne in mind as a diagnosis can never be made in isolation, especially in dermatopathology. In this article, we discuss in brief the various common cutaneous lymphoid infiltrative entities encountered in routine practice, discuss the differentiating features, and suggest an algorithmic approach to arrive at the possible diagnosis.